This How Rebels Spoke: a study on a sample of social and protest movement leaders in Egypt during the first decade of the 21st century.: This How Rebels Spoke - AbuAl-Khair, Omaima Mohammed (Al-Adab Journal, 2022)
Abstract This study sheds light on the resistance and change of the social and protest movement leaders in Egypt. It adopts the case study approach and in-depth interview guide as tools for gathering the data required. The study raises important questions such as: what are the most important effective social variables to form social and protest movements?; and what is the nature of relationship between these movements, the public and the power? The study confirms our inability to understand the social and protest movements aside from the state. It also explains the emergence of such movements within the model of (C.J.R.P) which reflects the ability of the state to achieve its functions (citizenship, justice, responsiveness, and protection). This relationship between these movements and the public has been explained in the light of the theory of opportunity and its hypotheses regarding the free racer, the free ride, and collective experiences.The findings reveal that the most important factor for emergence of such social and protest movements is due to the enormous failure of the state to perform its functions relative to citizenship, responsiveness, and protection. It also asserts that the means and mechanisms being used by these movements were totally intact and they did not resort to violence in order not to lose its legitimacy among the public.